Allergic diseases at the beginning of XXI century - Jahnz-Różyk, Karina (Przewodnik Lekarza/Guide for GPs, 2007)
The prevalence of allergic diseases is still increasing. However, the progress in pathomechanism, diagnosis and treatment of allergic diseases is observed. The mechanism of cross-reactive reactions in pollen-food syndrome was presented in this study. Additionally, new diagnostic method – microarray using recombinant allergens to detect allergen-specific serum immunoglobulin E was described. The recombinant allergens can be used to formulate optimal preparations for both diagnostic applications and specific casual immunotherapy. Recombinant DNA technology provides the possibility to create therapeutic vaccines containing only relevant allergic proteins. The progress in practical consideration and future of allergen specific immunotherapy were evaluated in this study. Moreover, clinical application of anti-IgE recombinant humanized monoclonal antibody for the treatment of severe and difficult allergic asthma was presented.